Controlling potassium channel activities: Interplay between the membrane and intracellular factors - Yi, B. Alexander (The National Academy of Sciences, 2001)
Neural signaling is based on the regulated timing and extent of channel opening; therefore, it is important to understand how ion channels open and close in response to neurotransmitters and intracellular messengers. Here, we examine this question for potassium channels, an extraordinarily diverse group of ion channels. Voltage-gated potassium (Kv) channels control action-potential waveforms and neuronal firing patterns by opening and closing in response to membrane-potential changes. These effects can be strongly modulated by cytoplasmic factors such as kinases, phosphatases, and small GTPases. A Kv α subunit contains six transmembrane segments, including an intrinsic voltage sensor. In contrast, inwardly rectifying potassium (Kir) channels have just two transmembrane segments in each of its four pore-lining α subunits. A variety of intracellular second messengers mediate transmitter and metabolic regulation of Kir channels. For example, Kir3 (GIRK) channels open on binding to the G protein βγ subunits, thereby mediating slow inhibitory postsynaptic potentials in the brain. Our structure-based functional analysis on the cytoplasmic N-terminal tetramerization domain T1 of the voltage-gated channel, Kv1.2, uncovered a new function for this domain, modulation of voltage gating, and suggested a possible means of communication between second messenger pathways and Kv channels. A yeast screen for active Kir3.2 channels subjected to random mutagenesis has identified residues in the transmembrane segments that are crucial for controlling the opening of Kir3.2 channels. The identification of structural elements involved in potassium channel gating in these systems highlights principles that may be important in the regulation of other types of channels.